CHILDREN SPEAKING SKILL BASED ON THE BIRTH ORDER - Astuti, Henny Puji (Universitas Negeri Semarang, 2015)
Speaking is one of the language skills. It becomes an important means of communication, from which interlocutors can understand the intended meanings. The children speaking skill is influenced by many factors, one of which is the birth order. It describes how a particular child is born from the same mother such as the eldest, the middle, and the youngest child. This will actually shape character and ability of the children. Based on its function, a language is a means of communication used by individuals in their interaction or relationship with others. The speaking ability is not only related to the birth order, but also some other factors such as intelligence. The middle child usually has more speaking skill compared to the eldest and youngest child. He/ she can communicate from different directions, and his/her position gives its benefits. The middle child can develop the speaking skill from parents, older brothers/ sisters, and younger brothers/ sisters. No matter the position of the child is, his/ her speaking ability can optimally be achieved if the parents provide opportunities to communicate and practice based on his/ her needs.